Mathematical Skills as Predictors of Students’ Performance in Secondary School Mathematics in Ogun State, Nigeria - Taiwo Abiodun; Asanre Akorede Ayoola; Chinaka Turayi (MASI Mandiri Edukasi, 2025)
Stakeholders in education must understand the relationship between students' mathematical performance and their mathematical skills in order to develop a more effective mathematics curriculum and education. It is on this basis that this study examined mathematical skills as a predictor of students’ performance in secondary school mathematics in Ogun State, Nigeria. The survey design used for this study was descriptive. The population of this study consisted of all Senior Secondary School Two (SSS2) students in Ogun State. Four hundred eighty (480) secondary school students from the SSS2 class comprised the study sample. In this study, simple random and purposeful sampling methods were used. Purposive sampling technique was used to select twelve (12) schools among secondary schools in Ogun State, while the simple random sampling technique was used to select forty (40) respondents from each school. For this study, two research questions were used. The instruments used for data collection are: Mathematics Performance Test (r = 0.762); Numerical Skills Test (r = 0.86); Spatial Reasoning Test (r = 0.78); and Problem-solving Style Questionnaire (r = 0.82). The results showed a significant positive relationship between mathematical skills and students’ performance in mathematics. The correlation of independent variables in relation to the performance of students in mathematics is as follows: Numerical skills (r=0.122,p<0.05); Spatial skills (r=0.182, p<0.05); and Problem-solving skills (r=0.139,p<0.05) respectively. It was further revealed that mathematical skills relatively contributed to students’ academic performance in mathematics. It was then concluded that mathematical skills are an important factor that enhances students’ performance in mathematics.